Antioxidant Effects of Rhodoxanthin from Potamogeton crispus L. on H2O2‐Induced RAW264.7 Macrophages Cells. Issue 1 (16th December 2022) - Fu, Cong; Dong, Hongchun; Wang, Xiaozhen; Wang, Huirui; Zheng, Yang; Ren, Dandan; He, Yunhai; Liu, Shu; Wang, Qiukuan
Abstract: Potamogeton crispus L. ( P. crispus ) is the type of a widely distributed perennial herbs, which is rich in rhodoxanthin. In this research work, five antioxidant indexes in vitro were selected to study the antioxidant activity of rhodoxanthin from P. crispus (RPC). A model of hydrogen peroxide (H2 O2 ) ‐induced oxidative damage in RAW264.7 cells was established to analyze the antioxidant effect and potential mechanism of RPC. The levels of ROS, MDA and the activities of oxidation related enzymes by H2 O2 were determined by enzyme linked immunosorbent assay (ELISA). The mRNA expression of Nrf‐2, HO‐1, SOD1 and SOD2 was measured by qRT‐PCR assay. According to the results, RPC had free radical scavenging ability for 2, 2‐diphenyl‐1‐trinitrohydrazine (DPPH), 2, 2'‐azinobis(3‐ethylbenzo‐thiazoline‐6‐sulfonic acid radical ion) (ABTS), hydroxyl radical and superoxide anion. RPC significantly decreased the level of MDA and ROS and LDH activity, while increased GSH level and activities of SOD, GSH−Px and CAT. It was showed that RPC could increase the mRNA expression of Nrf‐2, HO‐1, SOD1 and SOD2 in RAW264.7 cells in a dose‐dependently manner. In summary, RPC treatment could effectively attenuate the H2 O2 ‐induced cell damage rate, and the mechanism is related to the reduction of H2 O2 induced oxidative stress and the activation of Nrf‐2 pathway. Abstract :